Diagnostic Value of Ultrasonography and Laparoscopy in Undescended Testes - H Shafi (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Cryptorchidism or absence of one or both of testes in the scrotum (undescended testes) is the most common urologic disorder in children. Two major complications in this condition are infertility and malignancy. Most diagnostic imaging procedure is ultrasound, but in cases that testes are not seen in ultrasound, laparoscopy is very useful. The aim of this study was to assess diagnostic value of ultrasonography and laparoscopy in undescended testes.METHODS: This diagnostic study was performed on all patients with undescended testes in teaching hospitals of Babol University of medical sciences, Babol, Iran. All patients were referred to sonography, if testes were seen in sonography, these patients were candidate for open surgery but if testes were not seen in two different sonographies, the patients were candidate for laparoscopy. All information is gathered in questionnaire and then the results of sonography, open surgery and laparoscopy were compared together.FINDINGS: One hundred and eight patients with 131 undescended testes, aged between 1 and 42 years with mean age of 13.9±8.99 years were studied. 78.7% of patients had unilateral undescended testes and 21.3% had bilateral undescended testes. The unilateral undescended testes were left sided in 47% and right sided in 53%. Sensitivity and specificity of sonography for intraabdominal testes were 16% and 97%, respectively. Whereas, sensitivity and specificity of sonography for inguinal canal testes were 85% and 76%, respectively. Also, sensitivity and specificity of laparoscopy for intraabdominal and inguinal canal testes were 100%.CONCLUSION: The results showed that diagnostic laparoscopy has a high sensitivity and specificity. When intraabdominal testes are not diagnosed by sonography, laparoscopy can be helpful.